2013
DOI: 10.1093/annonc/mds245
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab and bevacizumab: preclinical data and phase II trial in recurrent or metastatic squamous cell carcinoma of the head and neck

Abstract: Cetuximab and bevacizumab are supported by preclinical observations and are well tolerated and active in previously treated patients with SCCHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 34 publications
2
98
2
1
Order By: Relevance
“…The selective tyrosine kinase inhibitors erlotinib and gefitinib function through EGFR-inhibition. The results of the present study support several previous studies, which suggested that EGFR activation regulates VEGF expression (63)(64)(65). This mechanism may provide an explanation for the decrease in VEGFR-1 expression though selective EGFR-inhibition in HNSCC 11A.…”
Section: ------------------------------------------------------------supporting
confidence: 91%
“…The selective tyrosine kinase inhibitors erlotinib and gefitinib function through EGFR-inhibition. The results of the present study support several previous studies, which suggested that EGFR activation regulates VEGF expression (63)(64)(65). This mechanism may provide an explanation for the decrease in VEGFR-1 expression though selective EGFR-inhibition in HNSCC 11A.…”
Section: ------------------------------------------------------------supporting
confidence: 91%
“…Numerous drugs are in the early stages of development for HNSCC treatment, including novel anti-EGFR small-molecule tyrosine kinase inhibitors, EGFR antisense molecules, and multiple add-on therapies to radiation and chemotherapy intended to decrease resistance to anti-EGFR agents (42)(43)(44)(45). In addition, numerous other anti-EGFR agents are currently being assessed in phases II and III clinical trials in different HNSCC therapeutic settings (46,47). As the targeted treatment group only had 3/20 patients with high expression of EGFR, the majority of the patients exhibited low expression of EGFR; consequently, those patients were not sensitive to cetuximab and nimotuzumab.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated evidence of vessel normalization and increased therapeutic uptake. [22][23][24] There are also a series of studies that demonstrate the opposite effect of decreased uptake of therapeutic following anti-VEGF administration. 25 The notion that there is a therapeutic window based on dose and time likely explains these discrepant findings.…”
Section: Discussionmentioning
confidence: 99%